Relationships between physical, morphological, and physiological characteristics of seeds developed at different positions of the ear of two maize (Zea mays L.) hybrids - Batistella, F.; Moro, F. V.; De Carvalho, N. M. (Ista, 2002)
Maize seeds developed at different portions of the ear of two hybrids (one, a large seeded, and the other a small seeded hybrid) were compared as to physical positions, morphological, and physiological characteristics viewing to gain information to be used during seed conditioning. The number of positions in the ear were 10, starting at the proximal and ending at the distal end. For the sake of simplification, the data were combined to refer to seeds of the proximal, the central and the distal sectors of an ear. Measurements made of the seeds as to shape (length, width, and thickness) and as to size (1,000 seeds weight) indicated that the round seeds growing at the distal sector are significantly smaller (mainly when thickness is considered) and lighter than those growing at the proximal sector. on the other hand, determinations of the physiological quality indicated that the round-proximal and the central seeds are equivalent and both significantly superior to the round-distal ones, Considering these significant differences as to size, shape, and physiological quality, a proposition of suppressing part of the round-distal from the totallity of the round seeds during the operations of seed conditioning is made.